Small lesions of the dorsal or ventral hippocampus subregions are associated with distinct impairments in working memory and reference memory retrieval, and combining them attenuates the acquisition rate of spatial reference memory. Issue 9 (14th April 2020) - Hauser, Jonas; Llano López, Luis H.; Feldon, Joram; Gargiulo, Pascual A.; Yee, Benjamin K.
Abstract: The importance of the hippocampus in spatial learning is well established, but the precise relative contributions by the dorsal (septal) and ventral (temporal) subregions remain unresolved. One debate revolves around the extent to which the ventral hippocampus contributes to spatial navigation and learning. Here, separate small subtotal lesions of dorsal hippocampus or ventral hippocampus alone (destroying 18.9 and 28.5% of total hippocampal volume, respectively) spared reference memory acquisition in the water maze. By contrast, combining the two subtotal lesions significantly reduced the rate of acquisition across days. This constitutes evidence for synergistic integration between dorsal and ventral hippocampus in mice. Evidence that ventral hippocampus contributes to spatial/navigation learning also emerged early on during the retention probe test as search preference was reduced in mice with ventral lesions alone or combined lesions. The small ventral lesions also led to anxiolysis in the elevated plus maze and over‐generalization of the conditioned freezing response to a neutral context. Similar effects of comparable magnitudes were seen in mice with combined lesions, suggesting that they were largely due to the small ventral damage. By contrast, small dorsal lesions were uniquely associated with a severe spatial working memory deficit in the water maze. Taken together, both dorsal and ventral poles of the hippocampus contribute to efficient spatial navigation in mice: While the integrity of dorsal hippocampus is necessary for spatial working memory, the acquisition and retrieval of spatial reference memory are modulated by the ventral hippocampus. Although the impairments following ventral damage (alone or in combination with dorsal damage) were less substantial, a wider spectrum of spatial learning, including context conditioning, was implicated. Our results encourage the search for integrative mechanism between dorsal and ventral hippocampus in spatial learning. Candidate neural substrates may include dorsoventral longitudinal connections and reciprocal modulation via overlapping polysynaptic networks beyond hippocampus.